Revision of the Hybobathus arx and Pelecinobaccha summa species groups (Diptera: Syrphidae) - Miranda, Gil Felipe Gonçalves (Zootaxa, 2017)
The morphologically similar Hybobathus arx and Pelecinobaccha summa species groups are revised and distinguished from each other. Four new species are described (H. avittatus sp. nov., H. luciane sp. nov., P. alia sp. nov. and P. impostor sp. nov.), and three new combinations (H. obsoletus comb. nov., H. persimilis comb. nov., and P. cubensis comb. nov.) and several synonimies are proposed: Baccha bivittata Curran = H. arx (Fluke), B. myrtella Hull and B. nectarina Hull = H. obsoletus (Curran), B. druida Hull = H. phaeopterus (Schiner), B. pandora Hull = P. cubensis (Macquart), and B. susio Hull = P. summa (Fluke). The lectotype and paralectotypes of B. phaeoptera Schiner are also designated. The female genitalia are described for all species, and the puparium of H. luciane sp. nov. is described too. New prey records for H. luciane sp. nov. and H. phaeopterus are presented. Picture multi-optional keys were produced and links to these keys, as well as traditional dichotomous keys, are presented in this paper to identify the groups and their species.